PRAKTIK PENGENDALIAN INTERNAL DALAM ERA DIGITAL: STUDI KUALITATIF PADA PERUSAHAAN JASA DI DKI JAKARTA - Widhiari, Luh Kemala Putri (PT. Samudra Solusi Profesional, 2026)
Digital transformation has fundamentally changed the way service companies manage operational processes and financial information. The increasing reliance on digital systems brings not only efficiency but also new risks related to data integrity, system reliability, and internal control effectiveness. This study aims to explore internal control practices in the digital era from the perspective of service companies operating in DKI Jakarta. Using a qualitative descriptive approach, this research employs a case study method. Data were collected through in-depth semi-structured interviews, observation, and document analysis involving management, accounting staff, and internal control functions. The findings reveal that internal control practices have shifted from predominantly manual controls to technology-based controls, such as system access restrictions, automated authorization, and real-time monitoring. However, digitalization also introduces challenges, including system dependency, limited human resource capabilities, and potential control gaps arising from technology misuse. This study contributes to the accounting and internal control literature by providing contextual insights into how internal control practices evolve in response to digitalization in service companies.